The Clinical Potential of Semisynthetic Penicillins in Acute Bacterial Otitis Media and Acute Bacterial Tonsillitis in Children in the Practice of ENT Doctor: Focus on Ospamox and Amoxsiclav® - V.I. Popovych (Zaslavsky O.Yu., 2015)
The wide prevalence of bacterial infections of upper respiratory tract, especially in childhood, the presence of complications that threaten the health and lives of patients necessitate the prescription of a rational systemic antibiotic therapy. Given the fact that in most cases the characteristics of the bacterial spectrum as an etiologic agent of these diseases is known, penicillin antibiotics are the first line in this pathology. On the example of two clinical cases, we have considered the use of suspension Ospamox (amoxicillin) and Amoxiclav® (amoxicillin clavulanate) in children with acute tonsillitis and acute otitis media, which demonstrated high efficacy and safety of treatment.